Rediscovering the anatomy of urban growth: The spatio-temporal evolution of building activity in a Mediterranean city. Issue 3 (27th May 2019) - Salvati, Luca
ABSTRACT: The impact of building cycles on recent expansions of Athens was assessed under the hypothesis that non-linear paths of urban growth result from sequential phases of economic growth and decline. Changes over time in building activity were examined by considering indicators derived from a local-scale analysis of building permits issued by Greek municipalities between 1990 and 2016. Relevant socioeconomic forces shaping spatio-temporal variability in building activity were identified by analyzing contextual indicators through inferential techniques and multivariate analysis. The results showed distinctive responses of real-estate local markets to economic cycles at the local scale in Athens, allowing for identification of short-term and long-term urban dynamics characteristic of expansion and recession waves. The most sensitive indicators to economic cycles in Athens were density of new buildings, average floors per new building, density of building additions, and number of building permits per inhabitant. Infrastructure-driven development, as a result of the 2004 Olympic Games, has produced relevant alterations in short-term patterns in the construction market, resulting in spatially-complex urbanization trends. The author concludes that local-scale indicators derived from building permit data provide insights into progressively complex dynamics of urban growth, with implications for regional planning and the design of sustainable development practices.